Contralateral Acupuncture for the Treatment of Phantom Limb Pain and Phantom Limb Sensation in Oncologic Lower Limb Amputee: A Case Report - Guo, Qin; Di, Zhong; Tian, Hong-fang; Zhang, Quan-ai (Frontiers in Neuroscience, 2021)
Phantom limb pain (PLP) and phantom limb sensation (PLS) are common and distressing sequelae of amputation. Current pain management following amputation is challenging and unsatisfying. In this case study, a 74-year-old woman underwent above-knee amputation because of the rhabdomyosarcoma in the right leg. Despite several analgesics, pain was poorly controlled. The phantom limb pain and sensation were immediately reduced by the contralateral acupuncture, and abolished after the third session with no side-effects, no relapse during the next 9 months. Contralateral acupuncture showed positive effect on PLP and PLS in this case, but more robust evidence would be needed to support the efficacy of this treatment technique for indication.